2023
DOI: 10.1186/s12985-023-02152-6
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-associated organs failure and inflammation: a focus on the role of cellular and viral microRNAs

Abstract: SARS-CoV-2 has been responsible for the recent pandemic all over the world, which has caused many complications. One of the hallmarks of SARS-CoV-2 infection is an induced immune dysregulation, in some cases resulting in cytokine storm syndrome, acute respiratory distress syndrome and many organs such as lungs, brain, and heart that are affected during the SARS-CoV-2 infection. Several physiological parameters are altered as a result of infection and cytokine storm. Among them, microRNAs (miRNAs) might reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 236 publications
0
3
0
Order By: Relevance
“…This gene is particularly studied in cancer, where, depending on its type, MAPK9 may act as both a tumor suppressor and inducer [ 58 ]. Studies have also shown low levels of MAPK9 in COVID-19 patients [ 59 , 60 ], suggesting its role in the induction and development of the inflammatory process regardless of the type of disease. Our study revealed an increased level of miR-1275 in HaCaT culture after the addition of CsA compared to culture with LPS alone.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is particularly studied in cancer, where, depending on its type, MAPK9 may act as both a tumor suppressor and inducer [ 58 ]. Studies have also shown low levels of MAPK9 in COVID-19 patients [ 59 , 60 ], suggesting its role in the induction and development of the inflammatory process regardless of the type of disease. Our study revealed an increased level of miR-1275 in HaCaT culture after the addition of CsA compared to culture with LPS alone.…”
Section: Discussionmentioning
confidence: 99%
“…Upon a viral infection, has-miR-146a is primarily produced to regulate the innate immune response and inflammation by negatively regulating the NF-κB pathway 60 , 61 . Therefore, its expression in COVID-19 decreases inflammatory disorders in target organs such as the lungs, heart, brain, skin, and underlying vascular disease 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Upon a viral infection, has-miR-146a is primarily produced to regulate the innate immune response and inflammation by negatively regulating the NF-κB pathway 60 , 61 . Therefore, its expression in COVID-19 decreases inflammatory disorders in target organs such as the lungs, heart, brain, skin, and underlying vascular disease 61 , 62 . The hsa-miR-146a-5p increase we observed in post-COVID-19 patients is an indication of the path to recovery, as the levels of IL-1, IL-6 and TNF-α cytokines are inversely correlated to has-miR-146a production 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%